(untitled) (Agroindustrial Science, 2025)
This study aimed to determine the optimal flight height for controlling Spodoptera frugiperda in maize (Zea mays L.) plantations using the Agras T40 drone. The research was conducted in Manabí, Ecuador, the experiment compared two UAV-based treatments (5 m and 7 m flight altitudes) with a conventional backpack sprayer control. The Agras T40, equipped with rotary atomizers, applied specific pesticide mixtures on August 30 and June 9, 2024. Plant damage assessments, using GNSS and photogrammetry, were conducted pre and post application. Statistical analyses, including paired t-tests and ANOVA with Tukey HSD post-hoc tests, were performed to evaluate treatment efficacy. Results demonstrated that the 7m UAV treatment significantly reduced fall armyworm infestation compared to the 5m treatment and the conventional control. The 5m treatment showed an increase in infestation, likely due to increased canopy disturbance affecting droplet adherence. The 7 m UAV treatment achieved control comparable to the conventional method, but offered advantages in precision, sustainability and operator safety. This study highlights the potential of UAVs, specifically the Agras T40, for efficient and targeted fall armyworm management in maize, reducing chemical inputs and minimizing environmental impact.